PENGARUH PIJAT BAYI TERHADAP FREKUENSI MENYUSU PADA BAYI - Siti Qomariah; Sara Herlina; Wiwi Sartika (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
The health of a child, especially infants and toddlers is an aspect of needs that must be considered by parents where children have qualities that are very important for family members and their nation. Infancy is also called the golden age or golden age as well as a critical period for the development of a baby at the age of 0-12 months. This study aims to determine the effect of baby massage on the frequency of breastfeeding. This study used a pre-experimental research design with a one group pretest and posttest research approach. The sampling technique used was purposive sampling. The sample in this study were 26 infants aged 0-12 months. The data analysis used was univariate and bivariate using the Wilcoxon pretest-posttest. The results of data analysis obtained a p-value of 0.000 (p <0.05) which indicates that Ha is accepted and Ho is rejected. Thus it can be concluded that there is an influence between Baby Massage on the Frequency of Breastfeeding in the Simpang Baru Health Center work area. It is recommended for mothers who have babies to be able to massage the baby as often as possible because the mother's touch can increase the frequency of breastfeeding the baby.